KEEFEKTIFAN PENGGUNAAN STRATEGI MNEMONIC AKRONIM DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS TOPIK CAHAYA - Resky Dwi Yunita; Eko Kuntarto; Andi Gusmaulia Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to 1) describe the use of acronym mnemonic strategy in improving students' memory. 2) describe the use of the acronym mnemonic strategy in improving students' ability to create acronyms. 3) describe the effectiveness of using the acronym mnemonic strategy in improving student learning outcomes in IPAS subjects on the topic of light. This research was conducted at SDN 17/I Rantau Puri in the 2024/2025 academic year. With a sample of 23 students. This research uses a quantitative approach with the type of ex post facto research. The population in this study were all grade V students of SDN 17/I Rantau Puri, totaling 23 students. The sampling technique used in this study was total sampling. Data collection techniques were carried out using memory test instruments and learning outcomes tests. The analysis techniques used were descriptive statistical analysis and inferential analysis. The results showed that 1) there was a significant increase in student memory, this was shown through the acquisition of the average score for the student memory test in the pretest of 51.30 while the posttest was 68.26. 2) there is a significant increase in the ability to make acronyms, this is shown through the acquisition of the average value for the test to make student acronyms in the pretest of 58.09 while the posttest amounted to 76.91. 3) there is a significant increase in student learning outcomes, this is shown from the results of the t test with the paired sample t-test, the t value is greater than the t table, namely 11.163> 2.073 and Sig. (2 tailed) = 0.000 <0.05, then H0 is rejected and Ha is accepted. Therefore, it can be concluded that the use of acronym mnemonic strategies can improve student learning outcomes in IPAS subjects on the topic of light. From the results of this study, it can be concluded that the use of the acronym mnemonic strategy is effective in improving student learning outcomes. Therefore, it is recommended for teachers and schools to strive to use learning with the acronym mnemonic strategy because it can improve student learning outcomes.